Exploring the Determinants of the China-Pakistan Economic Corridor and Its Impact on Local Communities - Nadeem Akhtar (SAGE Publishing, 2021)
The China-Pakistan Economic Corridor (CPEC), a major development project in China’s fast-evolving Belt and Road Initiative (BRI), is arguably the most comprehensive of the six BRI economic and infrastructure corridors on land. For Pakistan, it is perceived “as the harbinger of a new era of connectivity and integration” that will not only transform the region’s economic development but also the well-being of Pakistanis. It investigates the impact of CPEC as perceived by the local communities in its ZoI. It also evaluates CPEC’s potential challenges: public support and local communities’ concerns such as their awareness, acceptance, and ownership of CPEC. To accomplish our research objectives, we analyze original microdata from 1,585 respondents living proximate to propose CPEC route(s) of Khyber Pakhtunkhwa province, in Pakistan. After aggregating the data on the basis of age, education, income, and social status, we conduct descriptive, bivariate, and multivariate analyses in an attempt to answer three research questions. We find significantly high level of awareness of CPEC across the board in the older age group of respondents (i.e., 40 years or older), hereinafter referred to as mature, highly educated, that is, respondents with university education. Older respondents expect more environmental and economic benefits than younger respondents, even as the latter expect lower social change and effect on migration than do the former. However, those in the upper social class expect higher economic and political benefits from CPEC, compared with those in the lower social class—an early indication of possible elite capture.